Answer :

(a + 2)(a – 1)= a^{2} + [(2)+(-1)] a + [(2)×(-1)]

{ ∵(x + p)(x + q)= x^{2} +(p + q)x +(p × q)

Here x = a, p = 2, q = -1 }

= a^{2} +(2 – 1)a +(-2)

= a^{2} + 2a – a – 2

= a^{2} + a – 2

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation